Impact of nutritional status according to GLIM criteria on the risk of incident frailty and mortality in community-dwelling older adults. Issue 3 (March 2021) - Rodríguez-Mañas, L.; Rodríguez-Sánchez, B.; Carnicero, J.A.; Rueda, R.; García-Garcia, F.J.; Pereira, S.L.; Sulo, S.
Summary: Background & aims: Poor nutritional status leads to multiple adverse outcomes, but few studies have assessed its role as a risk factor for incident frailty and death in community-dwelling older adults. Hence, the aim of this paper is to assess the role of nutritional status using the Global Leadership Initiative on Malnutrition (GLIM) criteria in the risk of frailty and mortality in Spanish community-dwelling older adults. Methods: We used data from two waves (waves 2 (2011–2013) and 3 (2015–2017)) from the Toledo Study of Healthy Ageing, which is an observational, prospective cohort (average follow-up = 3.18 years) of 1660 older (≥65 years) adults living in the community. Nutritional status categories were defined according to the GLIM criteria, which uses a two-step approach. First, screening for malnutrition risk. Once positive, individuals were classified as malnourished according to some phenotypic (body mass index, grip strength and unintentional weight loss) and etiologic (disease burden/inflammation and reduced food intake or assimilation) criteria. Frailty was assessed using both the Frailty Index (FI) and Frailty Trait Scale (FTS). Mortality data was obtained through the National Death Index. Results: From the 1660 older adults, 248 participants (14.04%) were classified as 'at malnutrition risk' (AMR) and 209 (12.59%) as malnourished (MN). AMR and MN subjects were older and with worse functional status (frailer). Adjusted cross-sectional analysis showed an association between nutritional status and frailty by both FI and FTS. Adjusted longitudinal analyses showed that AMR was associated with higher risk of frailty, using both the FTS (OR: 1.262; 95% CI: 1.078–1.815) and the FI (OR: 1.116; 95% CI: 1.098–1.686), while being malnourished was associated with higher mortality risk (OR: 1.748; 95% CI: 1.073–2.849), but not with incident frailty at follow-up period. Conclusions: Nutritional status, assessed through GLIM, predicts in a dose-dependent manner the risk of frailty and death. Being at malnutrition risk predicts the risk of becoming frail at follow-up period, whereas being malnourished predicts mortality. These findings highlight the importance of assessing the nutritional status of community-dwelling older adults to identify the ones at risk of developing frailty or death and inform targeted nutrition-focused interventions.